THE EXPEDIENCY OF LUDO GAME ON SUBSTANCE PRESSURE MATERIAL TO IMPROVE STUDENTS SCIENTIFIC LITERACY - Mas Al Fath Imru’ul Qais As-Syauqi; An Maulida Fauziah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This research aims to describe the feasibility of the ludo game on substances pressure material to improve students’ scientific literacy skills based on validity, practicality, and effectiveness. This type of research is a developmental research using the ADDIE model. The research design used is one group pretest-posttest design conducted on 32 students of class VIII-I of SMPN 40 Surabaya. The results obtained are based on the validity of the ludo game getting the average percentage of 86.67% with decent category, the practicality of the ludo game in terms of the results of the students' responses obtained an average percentage of 99.73%, the results of the feasibility of learning obtain an average percentage of all phases of 92.59%, then the results of student activities that obtain an average percentage of 87.50%, the effectiveness of the ludo game in terms of the pretest results students get an average of 60.15, while the posttest results obtained an average of 84.30 with mastery learning outcomes of 71.87%, the completeness of the indicators on the posttest obtained results namely in the aspect of science content obtained a percentage of 91.40 %, in the aspect of the science context gained a percentage of 88.28%, and lastly in the aspect of science content obtained a press entage of 83.59%. The percentage increase in science literacy scores through the calculation of N-Gain scores obtained an average value of 0.59 in the medium category. Based on these results it can be concluded that the game of ludo on material pressure substances to improve students' scientific literacy skills is feasible based on validity, practicality, and effectiveness.